What is the Eisenhardt Method, really? - Eisenhardt, Kathleen M (Strategic organization, 2021)
This essay sharpens and refreshes the multi-case theory-building approach, sometimes termed The “Eisenhardt Method.” The Method’s singular aim is theory building, especially with multiple cases and theoretical logic. Its defining features (e.g. research questions without obvious answers, careful case selection, well-identified constructs and relationships, theoretical arguments, boundary conditions) reflect this aim. I begin with the influence of the 1980s, including grounded theorizing and case logic. Relying on exemplars, I illustrate the Method’s defining features. I also address common misconceptions (e.g. types of data, number of cases, performance emphasis). These miss the Method’s essence and imply a rigid template that does not exist. Instead, the Method’s relatively few defining features enable a wide variety of research possibilities. I conclude with what I would write today like a richer palette of research choices, more emphasis on time, and flexible philosophy of science. Yet the core message of theory building would remain.